HUBUNGAN KARAKTERISTIK DENGAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH DI LINGKUNGAN III DAN V KELURAHAN BAGAN DELI KECAMATAN MEDAN BELAWAN TAHUN 2012 - Tota Farida Erfinna; indra cahaya; surya dharma (Lingkungan dan Kesehatan Kerja, 2013)
Relationship of Responden Characteristics (Education, Income, Occupation Knowledge and Attitude) And The Management Of Solid Waste Management Program In Area III and V Bagan Deli, Medan Belawan sub-district. Solid waste management program is one of the programs of Ministry of Sea and Fishery in Medan Belawan sub-district. On its implementation, solid waste management program in area III and V yet done well. Lack of the participation of the society on solid waste management may be caused by less understanding on sorting out the rubbish of household. The objective of this research is to analyze the relationship of responden characteristics (education, income, occupation knowledge and attitude) and the management of solid waste management program in area III and V Bagan Deli, Medan Belawan sub-district. This research was analytical survey with cross sectional design. The population was the housewives living in area III and V Bagan Deli, Medan Belawan sub-district for 631 persons, and the sample was taken for 87 persons. The data of the characteristics (education, income occupation, knowledge and attitude), management program, and the participation of the people was taken through direct interview using questionnaire. The collected data then analyzed using chi-square test at α = 0,05.The resulth of research showed that statistically the characteristics include education (p-value = 0,028), occupation status (p-value= 0,000). Knowledge level (p-value=0,002), and attitude (p-value=0,000) has significant relationship not have significant influence to the participation of the society. It si suggested for the management program parties to improve socialization about solid waste management program in rder to get better understanding on the rubbish and to improve the participation of the people. Key word : Characteristics, Participation, Solid Waste